2001
DOI: 10.1093/emboj/20.17.4952
|View full text |Cite
|
Sign up to set email alerts
|

A moving DNA replication factory in Caulobacter crescentus

Abstract: The in vivo intracellular location of components of the Caulobacter replication apparatus was visualized during the cell cycle. Replisome assembly occurs at the chromosomal origin located at the stalked cell pole, coincident with the initiation of DNA replication. The replisome gradually moves to midcell as DNA replication proceeds and disassembles upon completion of DNA replication. Although the newly replicated origin regions of the chromosome are rapidly moved to opposite cell poles by an active process, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
162
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(188 citation statements)
references
References 39 publications
20
162
1
1
Order By: Relevance
“…Differential interference contrast (DIC) and fluorescence microscopy were performed as described previously (Jensen et al, 2001;Ryan et al, 2002). Cells were placed on pads composed of 1% agarose in water or minimal media for examination.…”
Section: Microscopymentioning
confidence: 99%
“…Differential interference contrast (DIC) and fluorescence microscopy were performed as described previously (Jensen et al, 2001;Ryan et al, 2002). Cells were placed on pads composed of 1% agarose in water or minimal media for examination.…”
Section: Microscopymentioning
confidence: 99%
“…At the swarmer cell stage, which is characterized by a quiescent chromosome and, therefore, equivalent to the G 1 -phase of the cell cycle, the origin and terminus are located at the two opposite poles of the cell. After assembly of the replisome at the polar origin and initiation of DNA synthesis in the newly differentiated stalked cell, the duplicated strands are rapidly segregated, with one origin staying at the original position, while the second moves to the other end of the cell [Jensen and Shapiro, 1999;Jensen et al, 2001;Viollier et al, 2004]. As replication continues, the replisome is gradually displaced from its Viollier et al [2004] showed that the subcellular position of chromosomal sites is linearly dependent on their distance on the chromosomal map from the origin of replication.…”
Section: Dynamics Of the Replication Processmentioning
confidence: 99%
“…initially polar position to the division plane [Jensen et al, 2001]. Examination of the movement and cellular positioning of individual chromosomal loci during the course of replication revealed that duplicated DNA segments are immediately recondensed and rapidly moved in opposite directions to assume their final positions in the incipient daughter cells.…”
Section: Dynamics Of the Replication Processmentioning
confidence: 99%
“…In accordance with the organization of the chromosome within the bacterial cell, replication in E. coli and B. subtilis initiates at or near mid-cell (Lemon and Grossman 1998;Bates and Kleckner 2005;Reyes-Lamothe et al 2008), whereas in C. crescentus replication initiates at the cell pole (Jensen et al 2001). The cellular "marks" that direct the replisomes to these positions appear to be the origin itself rather than extrinsic localization determinants.…”
Section: Replication In Bacteria and Eukaryotesmentioning
confidence: 92%
“…However, accumulating evidence over the last decade suggests that after replication initiation, the replisomes are not stationary nor do they cluster (Jensen et al 2001;Bates and Kleckner 2005;Berkmen and Grossman 2006;Reyes-Lamothe et al 2008). Instead, it appears that the nucleoid serves as both the template and track for the replication machinery.…”
mentioning
confidence: 99%